Managing risks and harms associated with the use of anabolic steroids: a qualitative study - J. M. X. Amaral; A. Kimergård; P. Deluca (Harm Reduction Journal)
Abstract Background People using anabolic steroids adopt different strategies to manage risks and harms associated with the use of these substances. We investigated how users learn, develop and incorporate risk-management strategies, as well as the events triggering changes in their health-related behaviour. Methods Twenty semi-structured interviews were conducted with anabolic steroid users living in the UK to discuss their risk-management strategies (19 males, 1 female; median age = 35.5 years; median time of anabolic steroid use = 9 years). Online interviews were transcribed verbatim and qualitative data was analysed via iterative categorisation. Results The use of risk-management strategies was characterised as a continuous cycle of identification, prevention and control of risks and harms. Preventative strategies were more commonly adopted after many years of anabolic steroid use. Changes in life circumstances and adverse health conditions were described as common triggers for changes in behaviour, including the cessation of anabolic steroid use. Conclusion Our findings can inform interventions aimed at increasing awareness and promoting healthier behaviours among people who use anabolic steroids. Further research is needed to evaluate the effectiveness and safety of the risk-management strategies employed by this population.